Analisis Faktor Fasilitas Customer Relation Management Terhadap Pertimbangan Konsumen Pada Shopeefood - Dani Iqbal Azhari; Yohanes Suhari (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Many consumer considerations in choosing, buying an item to meet their needs in buying at online stores. One of the online stores is Shopee, Shopee has several features, one of which is the Shopeefood feature. This study aims to find the component factors of Cutomer Relationship Management (CRM) that consumers consider when choosing Shopeefood. The tool for collecting research data is in the form of questionnaires distributed to Shopeefood consumers who live in the city of Semarang with a total of 120 respondents. This research method uses the Exploratory Factor Analysis (EFA) method. The results of this study found that the factors taken into consideration in choosing Shopeefood were Shopeefood's commitment, communication facilities, service quality, ease of accessing applications. Shopeefood's commitment in question, especially the assistance and attention provided by employees, on communication facilities, namely there is clear information from the company, on service quality, namely information provided by CS can help understand shopeefood transactions, on the ease of accessing applications, namely the shopeefood display that easy to understand.